The disposition effect when deciding on behalf of others - Daniel Hermann; Oliver Mußhoff; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
The disposition effect is a well-established phenomenon which describes the behavior of investors that are more willing to sell capital gains than capital losses. In this article we present experimental evidence on a situation where an investor decides on behalf of another person. In our setting, trading effort should only be affected by investors' intrinsic motivation, as trading actions only influence the profits of a matched person. In a control treatment, trades directly influence investors' profits. Overall, we find that trading on behalf of others increases disposition effects. In this treatment, we find that the effect is caused by inexperienced investors, characterized by a greater concern for others. Thus, trading for others results in an emotional burden for these investors, which leads to weak trading performance.
Keywords: C91; D14; D81; G41; 330; disposition effect; experiment; decisions on behalf of others; social value orientation; loss aversion